RELEVANSI PRINSIP EKONOMI ISLAM DALAM PEMBINAAN UMAT ISLAM - Reni Ria Armayani Hasibuan (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2021)
Indonesia is one of the developed countries with abundant natural wealth, because these abundant natural resources make Indonesia a country that can be relied on. However, in reality there are still many people who belong to the poor, who live in poverty. This becomes a big question, why does this happen? What's wrong with the economic system? departing from this, this article takes a decision taken from an economic system that is still wrong, namely using a capitalist system, so that a deeper study is needed to study the Islamic economic system as a solution to create prosperity for society. This article also affirms that Islamic Economics is dynamic, and not compartmentalized, in the sense that Islamic Economics provides blessings for all levels of society. This is because Islamic Economics makes Al Quran and As Sunnah as the basis of its implementation, coupled with ijtihad and the increasing thinking of experts in the field of Islamic economics that Islamic Economics is the best solution as a way out of poverty and economic decline.